2000
DOI: 10.1152/ajprenal.2000.279.3.f502
|View full text |Cite
|
Sign up to set email alerts
|

Vasopressin-dependent upregulation of aquaporin-2 gene expression in glucocorticoid-deficient rats

Abstract: We determined alterations in renal aquaporin-2 (AQP2) gene expression in association with impaired water excretion in glucocorticoid-deficient rats. After adrenalectomy, Sprague-Dawley rats were administered aldosterone alone by osmotic pumps (glucocorticoid-deficient rats). As a control, both aldosterone and dexamethasone were administered. These animals were subjected to the studies on days 7-14. The expressions of AQP2 mRNA and protein in kidney of the glucocorticoid-deficient rats were increased by 1.6- an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
48
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 34 publications
5
48
0
1
Order By: Relevance
“…In experimental models of glucocorticoid deficiency non-suppressible release of AVP is found despite hypo-osmolality, which should suppress AVP release to undetectable levels (5 -7). We have demonstrated that the AVP V 2 receptor antagonist blocked the upregulation of AQP-2 mRNA expression and promptly normalized renal water excretion in glucocorticoid-deficient rats (12). Also, similar results were obtained with hydrocortisone replacement in glucocorticoid-deficient rats and patients with hypopituitarism, i.e.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…In experimental models of glucocorticoid deficiency non-suppressible release of AVP is found despite hypo-osmolality, which should suppress AVP release to undetectable levels (5 -7). We have demonstrated that the AVP V 2 receptor antagonist blocked the upregulation of AQP-2 mRNA expression and promptly normalized renal water excretion in glucocorticoid-deficient rats (12). Also, similar results were obtained with hydrocortisone replacement in glucocorticoid-deficient rats and patients with hypopituitarism, i.e.…”
Section: Discussionsupporting
confidence: 77%
“…Also, similar results were obtained with hydrocortisone replacement in glucocorticoid-deficient rats and patients with hypopituitarism, i.e. hydrocortisone replacement normalizes AVP secretion, urinary excretion of AQP-2 and water diuresis (4,6,9,10,12,22). Therefore, non-suppressible secretion of AVP plays a crucial role in impaired water excretion in secondary adrenal insufficiency.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Finally, peptide (7) and nonpeptide V 2 receptor antagonists (23) have been shown to dramatically enhance the renal capacity to excrete solute-free water in GD. Thus the nonosmotic release of AVP during GD may involve direct hypothalamic and peripheral baroreceptor pathways.The effect of GD on renal AQP2 expression is less clear (11,23). However, in a recent study, Saito et al (23) demonstrated an AVP-dependent increase in renal medullary AQP2 expression in GD rats.…”
mentioning
confidence: 99%